The Longer The Shifts For Hospital Nurses, The Higher The Levels Of Burnout And Patient Dissatisfaction - Stimpfel, Amy Witkoski; Sloane, Douglas M.; Aiken, Linda H. (Health Affairs, 2012)
Extended work shifts of twelve hours or longer are common and even popular with hospital staff nurses, but little is known about how such extended hours affect the care that patients receive or the well-being of nurses. Survey data from nurses in four states showed that more than 80 percent of the nurses were satisfied with scheduling practices at their hospital. However, as the proportion of hospital nurses working shifts of more than thirteen hours increased, patients' dissatisfaction with care increased. Furthermore, nurses working shifts of ten hours or longer were up to two and a half times more likely than nurses working shorter shifts to experience burnout and job dissatisfaction and to intend to leave the job. Extended shifts undermine nurses' well-being, may result in expensive job turnover, and can negatively affect patient care. Policies regulating work hours for nurses, similar to those set for resident physicians, may be warranted. Nursing leaders should also encourage workplace cultures that respect nurses' days off and vacation time, promote nurses' prompt departure at the end of a shift, and allow nurses to refuse to work overtime without retribution.